Timing of hemodynamic changes during transnasal endoscopic surgery. (4th November 2015) - Naunheim, Molly; Yung, Katherine C.; Courey, Mark
Abstract : Objectives/Hypothesis: Although considered less invasive and therefore less morbid than laryngoscopy under general anesthesia, prior research shows that transnasal flexible endoscopic (TNFE) procedures are associated with a significant increase in heart rate and blood pressure. The purpose of this review was to identify the most stimulating portion of the procedure to potentially provide a target for directed pharmacotherapy to ensure hemodynamic stability. Study Design: Retrospective chart review. Methods: Retrospective chart review of adult patients who underwent upper airway intervention in the larynx and trachea by TNFE. Vital signs recorded at 5‐minute intervals throughout the procedure were examined and analyzed by Wilcoxon signed rank test and Wilcoxon rank sum test. Results: For heart rate and systolic and diastolic blood pressure, the median change in value was 13 beats per minute ( P  < 0.0001), 27 mm of mercury ( P  < 0.0001), and 26.5 mm of mercury ( P  < 0.0001), respectively. The most significant change in heart rate and saturation was during the application of nasal and laryngeal anesthetic, as well as during the positioning of the scope. Blood pressures were elevated during the procedure itself. With respect to comorbidities, underlying asthma and coronary artery disease were associated with a greater percent change in the heart rate ( P  = 0.05 for both). Conclusion: There are significant vital sign changes during transnasal endoscopic procedures. Changes in heart rate and oxygen saturation tended to occur during preparation, whereas blood pressure was elevated during the laryngeal intervention. For patients with asthma, the percent change was greater, and perhaps a more controlled environment is warranted. Level of Evidence: 4. Laryngoscope, 126:2047–2050, 2016